Credere alla carne La funzione del corpo nel cinema di genere e documentario (Altre Modernità, 2021)
What is the cinema of the body? And the cinema of the animal-body? And again: can cinema give us the presence of the body? On the basis of the Deleuzian concept of the cinematographic body, in this essay I will try to conduct – with the help of some exemplary films, “genre” and author films – an analysis of the cinema of the body and of the animal-body which, through the representation of monstrous bodies and expendable bodies, of animal and animalized bodies, through the becoming animal of visible and invisible bodies, can help to restore the discourse to the body, to bring to light a new narrativity of the body of the living and to force the viewer to believe in the body, in the bodies, to believe in the flesh: since the cinema of the animal-body is always political cinema, as such it can lead to political action, an action understood as a change in our posture in the face of otherness.
Keywords: cinema; body; flesh, animal; narrativity; institution